A new microporous 12-ring zincosilicate THK-2 with many terminal silanols characterized by automated electron diffraction tomography. Issue 37 (16th September 2020) - Sakamoto, Yasuhiro; Zhao, Haishuang; Gies, Hermann; Yamamoto, Katsutoshi; Kolb, Ute; Ikeda, Takuji
Abstract : The crystal structure of a new microporous zincosilicate THK-2 was elucidated by using the automated electron diffraction tomography (ADT) approach. The framework of THK-2 consisted of 4-, 5-, 6-, and 12-rings and included a disordered ZnO4 . Abstract : A newly synthesized microporous zincosilicate THK-2 (estimated structural composition: |(H2 O)6.7 (C6 H13 N)0.9 |[Li0.5 Zn3.1 Si32 O62.7 (OH)9.3 ]) was characterized by single-crystal electron diffraction using the automated electron diffraction tomography (ADT) approach in combination with powder X-ray diffraction. The lattice constants and space group of as-synthesized THK-2 were a = 2.50377(7) nm, b = 1.43866(4) nm, c = 0.505369(8) nm, and Pccn (no. 56) with orthorhombic symmetry. Because the crystal lattice was almost identical to a hexagonal lattice ( ), the first several peaks in its powder X-ray diffraction data severely overlapped, which suppressed the structural information to decide the framework topology. In order to overcome this intrinsic difficulty, the structure model of THK-2 was initially obtained by the direct method based on ADT data and refined by the Rietveld method. Its 3-dimensional framework structure was elucidated and it consisted of 4-, 5-, 6-rings of tetrahedral Si and Zn atoms and a one-dimensional straight channel with a 12-ring pore opening. Zn atoms were incorporated into the framework as four-coordinated [ZnO4 ], although their distribution was confirmed to be disorderly. In the as-synthesized THK-2, the site occupancy of Zn was as low as 0.39; that is, more than 60% of the Zn sites were vacant. Hexamethyleneimine and water molecules were accommodated in the straight channel in a disordered manner. The material was stable upon calcination, and the BET specific surface area and micropore volume of calcined THK-2 were 240.6 m 2 g −1 and 0.12 ml g −1, respectively.